Evasão escolar em uma unidade de ensino médio e técnico: as Etecs em um novo significado - Nedelciu, Jeferson (Universidade Federal de São Carlos, 2023)
School dropout is a phenomenon present in our society and identified as one of the most serious problems of education in the country. Despite many studies in the area and a series of hypotheses raised, the topic still lacks clear answers. It is possible to note that there is a certain “common sense” when it comes to evasion, in which many researchers always point out a direction to identify the culprits in the process. However, evasion is complex and permeated with aspects in which even to simply define what evasion is, we have already found disagreements between researchers. In parallel, school dropout discussions are almost always directed at elementary, middle and/or higher education levels; little is produced or discussed about school dropout in technical education. Technical education, today, is an extremely important teaching modality in our society and moves the lives of thousands of young people and adults in Brazil. For contextualization, this study will take place exclusively in a high school and technical school, called Etec (State Technical School): the unit has about two thousand students enrolled, but is part of the State Center for Technological Education Paula Souza (CEETEPS), autarchy of Government of the State of São Paulo, which currently has more than 230,000 enrollments per semester. Therefore, we have in technical education a huge movement of young people and adults who are seeking in this institution the professionalization process and other “benefits” that are expected in schooling. However, technical education schools are built from the perspective of social change through professionalization. This fact presents us with discussions about the commodification of education, as well as the problems generated by meritocracy in education. For the development of the research, young people between 15 and 17 years old who were enrolled at Etec, between 2016 and 2021, and who dropped out of the technical course in the period were sought. The historical clipping was intended to pick up students who were present during the period of imposition of the high school reform, enacted by Law nº 13.415/2017, and to those who have been under the changes caused by the Covid-19 Pandemic. The result of the research points out that we are going through a great change in the profile of the young people who are present in the secondary and technical education units of the Etecs. By far, the public is no longer the one identified in the mid-1980s, when technical education was aimed at the marginalized, with technical training being their only possible professional training. Therefore, new demands are present in the lives of these young people, and their aspirations, if different from what is imposed in the technical school, are reflected in their evasion. Therefore, a school education focused on the labor market and having the principle of individual merit as a prominent source, disregarding the inequalities of our society, needs to be rethought and discussed.
School dropout in a high school and technical education unit: the Etecs in a new meaning
Deserción escolar en un secundario y unidad de educación técnica: las Etecs en un nuevo significado
Keywords: Ensino Técnico; Educação; Juventude; High School; school dropout; Technical Education; CIENCIAS HUMANAS::EDUCACAO